Industrial engineering and management science : proceedings of the 2014 International Conference on Industrial Engineering and Management Science (IEMS 2014), 8-9 August 2014, Hong Kong - Lee, Garry (Writer on engineering) (Communications in information engineering, 2015)
The 2014 International Conference on Industrial Engineering and Management Science (IEMS 2014) was held August 8-9, 2014, in Hong Kong. This proceedings volume assembles papers from various professionals, leading researchers, engineers, scientists and students and presents innovative ideas and research results focused on Industrial Engineering and Management Science. The papers in this book group around the following topics: Information Technology, Industrial Development and Industrial Engineering and Performance Evaluation.